2008
DOI: 10.1159/000127443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-Allocryptopine on Transient Outward Potassium Current in Rabbit Ventricular Myocytes

et al.

Abstract: Objective: To investigate the mechanism of α-allocryptopine-induced inhibition of the transient outward potassium current (Ito) in rabbit left-ventricular myocytes. Methods: We used the whole-cell patch-clamp technique to record the Ito in the myocytes, which were isolated from the rabbit left ventricle by a Langendorff-perfusion device. Results: Allocryptopine decreased the amplitude and the density of the Ito in a concentration-dependent (range from 1 to 100 µM with an IC Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In guinea pig atria this elevates intracellular Na + , activating the Na + /Ca 2+ exchanger resulting in increased intracellular Ca 2+ levels, a 10 μM dose having a positive inotropic effect [ 181 ]. Protopine acts as a promiscuous cation channel inhibitor in guinea pigs blocking Ca 2+ , K + and Na + ion channels [ 182 ], while allocryptopine blocks K + channels in rabbit ventricular myocytes [ 183 ]. Allocryptopine is more effective than quinidine in preventing induced arrhythmias in rats [ 184 ].…”
Section: Biological Activities Of S Canadensis mentioning
confidence: 99%
“…In guinea pig atria this elevates intracellular Na + , activating the Na + /Ca 2+ exchanger resulting in increased intracellular Ca 2+ levels, a 10 μM dose having a positive inotropic effect [ 181 ]. Protopine acts as a promiscuous cation channel inhibitor in guinea pigs blocking Ca 2+ , K + and Na + ion channels [ 182 ], while allocryptopine blocks K + channels in rabbit ventricular myocytes [ 183 ]. Allocryptopine is more effective than quinidine in preventing induced arrhythmias in rats [ 184 ].…”
Section: Biological Activities Of S Canadensis mentioning
confidence: 99%
“…Both of the drugs have electrophysiological effects that may contribute to the prolongation of the APD. In previous studies [14] , we demonstrated that ALL possesses an inhibition effect on I to in a frequencydependent manner and decreases the transmural gradient of I to . BTHP inhibits the I Kr and the slowly delayed rectifier potassium current (I Ks ) in a frequency-dependent manner.…”
Section: Introductionmentioning
confidence: 64%
“…In other reports, we demonstrated that the threshold doses of aconitine and calcium chloride that induced ventricular ectopic beats, ventricular tachycardia and ventricular fibrillation in rats were increased by ALL. The electrophysiological measurements of ALL showed a prolongation of APD in the rabbit heart [14,15] . We have also found that ALL exerted an inhibition effect on the transient outward potassium current (I to ) in a frequencydependent manner and decreased the transmural gradient of I to [16] .…”
Section: Discussionmentioning
confidence: 99%
“…PRO also attenuates and prevents LPS-induced inflammatory damage via TRL4 and MAPK/NF-kappa B ( 79 , 80 ). Few studies have examined ALL, although some have reported its potential antiarrhythmic activity ( 81 83 ). Only one study reported the protective effect of ALL against oxidative stress-induced neuronal damage ( 84 ).…”
Section: Discussionmentioning
confidence: 99%